2011
DOI: 10.1007/s11626-011-9467-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and semiquantitative immunoassay of growth factors and cytokines in the conditioned medium of STO and CF-1 mouse feeder cells

Abstract: Feeder cells of irradiated mouse fibroblasts are commonly used for, and are generally necessary for, the in vitro maintenance and growth of many fastidious cell types, particularly embryonic stem cells or induced pluripotent stem cells. Quantitative and semiquantitative immunoassays of conditioned media were performed to identify some of the soluble cytokines, chemokines, protein hormones, and cell matrix/adhesion molecules that are elaborated from two commonly used feeder cells, STO and CF-1. Among those quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 60 publications
1
22
0
Order By: Relevance
“…An intriguing possibility is that upregulation of KIT expression, which occurred after miR-221/222 inhibition, allowed for activation of signaling from KIT ligand (KITL), thereby causing irreversible loss of stem cell potential. Maintenance of THY1 + undifferentiated spermatogonia as a proliferative stem cellcontaining population in vitro requires co-culture with feeder cell monolayers and in this study we utilized STO feeder cells, which are known to secrete KITL (Lim and Bodnar, 2002;Talbot et al, 2012). These results indicate that the stem cell capacity of spermatogonia is linked to miR-221/222 abundance.…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…An intriguing possibility is that upregulation of KIT expression, which occurred after miR-221/222 inhibition, allowed for activation of signaling from KIT ligand (KITL), thereby causing irreversible loss of stem cell potential. Maintenance of THY1 + undifferentiated spermatogonia as a proliferative stem cellcontaining population in vitro requires co-culture with feeder cell monolayers and in this study we utilized STO feeder cells, which are known to secrete KITL (Lim and Bodnar, 2002;Talbot et al, 2012). These results indicate that the stem cell capacity of spermatogonia is linked to miR-221/222 abundance.…”
Section: Research Articlementioning
confidence: 99%
“…Here, we used qRT-PCR analysis to measure changes in the abundance of miR-221 and miR-222 in cultured THY1 + undifferentiated spermatogonia following individual exposure to extrinsic factors. The maintenance of these cells as a proliferative stem cell-containing population in vitro requires supplementation of culture media with GDNF and FGF2, and co-culture with feeder cells that secrete other factors including CSF-1 (Lim and Bodnar, 2002;Talbot et al, 2012). Therefore, we removed the germ cell clumps from feeder cell monolayers and…”
Section: Expression Of Mir-221/222 In Undifferentiated Spermatogonia mentioning
confidence: 99%
“…Amniotic membrane is rich in stromal cells and secretes cytokines and growth factors, such as SCF, HGF and IGF, that are produced by cell lines (i.e. STO and CF-1) usually employed as feeder layer in vitro for ESC expansion52. Moreover, Bashamboo et al 53 showed that in vitro ESC differentiation is dependent on the SCF-KIT pathway, and Chen et al 54 demonstrated how a signalling by vitamin A/retinol promotes the self-renew of ESC through the activation of PI3K/Akt signalling via IGF-1 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the mitotic inactivation or irradiation of MEFs stimulates the expression of several signaling proteins, such as Wnt-3 [16], which may participate in the molecular mechanisms underlying the maintenance of pluripotency in co-cultured human ESCs/iPSCs. The outbred mouse CF-1 strain may be the most widely used donor for MEF feeder cells for ESC and iPSC culture [13,17], as CF-1 MEFs have been shown to produce TGF-β1, activin A, BMP-4, gremlin, and noggin [14,18,19] but not bFGF [14]. One disadvantage of using primary MEFs is their limited proliferation capacity, which requires repeated isolation from embryonic mice to supply feeder cells [20].…”
Section: Mouse-derived Feeder Cellsmentioning
confidence: 99%
“…Proteome analyses have revealed that STO cells produce unique protein species, such as insulin-like growth factor binding protein 4 (IGFBP-4), pigment epithelium-derived factor (PEDF) and secreted protein acidic and rich in cysteine (SPARC, also known as osteonectin), which may be associated with differentiation and cell growth [26]. Talbot et al [17] showed from quantitative immunoassays that STO cells express lower levels of activin A, interleukin-6, IGFBP-2, IGFBP-3, IGFBP-4, and IGFBP-5 than CF-1 cells but higher levels of hepatocyte growth factor (HGF) and stem cell factor (c-kit ligand). The difference in the growth factor production among feeder cell types may result in different abilities to support the growth of undifferentiated human ESCs/iPSCs.…”
Section: Mouse-derived Feeder Cellsmentioning
confidence: 99%